Recent advances in combinatorial cancer prevention, prognosis, diagnosis, imaging, screening, treatment and management via multi–functionalized ruthenium (IV) oxide (RuO2) and ruthenium (VIII) oxide (RuO4) nanoparticles under synchrotron and synchrocyc - Heidari , Alireza; Hotz , Margaret; MacDonald , Nancy; Peterson , Victoria; Caissutti , Angela; Besana , Elizabeth; Esposito , Jennifer; Schmitt , Katrina; Chan, Ling-Yu; Sherwood , Francesca; Henderson , Maria; Kimmel , Jimmy (International Journal of Advanced Chemistry, 2022)
In the current research, recent advances in combinatorial cancer prevention, prognosis, diagnosis, imaging, screening, treatment and management via multi–functionalized Ruthenium (IV) Oxide (RuO₂) and Ruthenium (VIII) Oxide (RuO4) nanoparticles under synchrotron and synchrocyclotron radiations is investigated. The calculation of thickness and optical constants of Ruthenium (IV) Oxide (RuO₂) and Ruthenium (VIII) Oxide (RuO4) recent advances in combinatorial cancer prevention, prognosis, diagnosis, imaging, screening, treatment and management via multi–functionalized Ruthenium (IV) Oxide (RuO₂) and Ruthenium (VIII) Oxide (RuO4) nanoparticles under synchrotron and synchrocyclotron radiations produced using sol–gel method over glassy medium through a single reflection spectrum is presented. To obtain an appropriate fit for reflection spectrum, the classic Drude–Lorentz model for parametric di–electric function is used. The best fitting parameters are determined to simulate the reflection spectrum using Lovenberg–Marquardt optimization method. The simulated reflectivity from the derived optical constants and thickness are in good agreement with experimental results.Recent advances in combinatorial cancer prevention, prognosis, diagnosis, imaging, screening, treatment and management via multi–functionalized Ruthenium (IV) Oxide (RuO₂) and Ruthenium (VIII) Oxide (RuO4) nanoparticles under synchrotron and synchrocyclotron radiations
Keywords: Cancer Prevention; Prognosis; Diagnosis; Imaging; Screening; Treatment and Management; Ruthenium (IV) Oxide (RuO₂) and Ruthenium (VIII) Oxide (RuO4) Nanoparticles; Synchrotron and Synchrocyclotron Radiations.